An Unusual Etiology of Graves’ Disease: Alemtuzumab - Santiago Carrion, Ada Marie (J Endocr Soc, 2021)
Cluster of differentiation 52 (CD-52) is a glycoprotein expressed on the surface of most lymphocytes and it is the most prevalent marker in T cells, B cells, natural killers and monocytes. Alemtuzumab, a CD-52 monoclonal antibody, is one of the initial therapies approved for patients with relapsing-remitting multiple sclerosis. It acts by inducing rapid and prolonged depletion of lymphocytes with a consequent immunosuppression. Although not clearly understood, Alemtuzumab has been associated with the development of autoantibodies. These have been reported to cause thyroid injury resulting in 10-15% incidence of new-onset Graves’ disease. This is the case of a 38 year-old man with medical history of relapsing-remitting multiple sclerosis who came to the Endocrinology clinic to establish care due to abnormal thyroid function tests. Patient has received Alemtuzumab since the past two years. Three months prior to arrival, he was found with weight loss, hyperdefecation and tremors by his Neurologist. Patient was found with suppressed TSH for which Methimazole was commenced. Thyroid ultrasound showed normal size and homogenous right and left thyroid lobes, and no evidence of cystic or solid masses. Thyroid stimulating immunoglobulins were found elevated which correlated with Graves’ disease. Moreover, thyroid scintigraphy showed 34% radioiodine uptake at 24 hours indicating de novo synthesis of thyroid hormone in this patient with hyperthyroidism. As Alemtuzumab was identified as a precipitating cause of Graves’ disease, therapy was discontinued and plasmapheresis will be given for the treatment of relapsing-remitting multiple sclerosis. Monoclonal antibody use has increased since the past decades. It has been well described in literature that monoclonal antibodies against programmed cell death receptor 1 (PD-1) and programmed cell death ligand 1 (PD-L1) may cause autoimmune thyroid disease. Nonetheless, it is important to recognize that other monoclonal antibodies may have similar adverse effects. Alemtuzumab is a monoclonal antibody and antineoplastic agent used for relapsing multiple sclerosis, some hematologic malignancies, and as an induction agent for solid organ transplantation. Its main effects include autoimmunity with thyroid being one of the most described targets. In these patients, expert clinicians should recognize the possibility of thyroid disease for prompt treatment which will improve quality of life.